Characterizing the aerosol atmosphere above the Observatorio del Roque de los Muchachos by analysing seven years of data taken with an GaAsP HPD-readout, absolutely calibrated elastic LIDAR. Issue 3 (15th June 2022) - Fruck, Christian; Gaug, Markus; Hahn, Alexander; Acciari, Victor; Besenrieder, Jürgen; Dominis Prester, Dijana; Dorner, Daniela; Fink, David; Font, Lluís; Mićanović, Saša; Mirzoyan, Razmik; Müller, Dominik; et al.
ABSTRACT: We present a new elastic LIDAR concept, based on a bi-axially mounted Nd:YAG laser and a telescope with HPD readout, combined with fast FADC signal digitization and offline pulse analysis. The LIDAR return signals have been extensively quality checked and absolutely calibrated. We analyse seven years of quasi-continuous LIDAR data taken during those nights when the MAGIC telescopes were operating. Characterization of the nocturnal ground layer yields zenith and azimuth angle dependent aerosol extinction scaleheights for clear nights. We derive aerosol transmission statistics for light emitted from various altitudes throughout the year and separated by seasons. We find further seasonal dependencies of cloud base and top altitudes, but none for the LIDAR ratios of clouds. Finally, the night sky background light is characterized using the LIDAR photon backgrounds.